THE EFFECTIVENESS OF THE MNEMONIC METHOD ON THE ABILITY TO READ HIJAIYAH LETTERS IN MENTALLY DISABLED CHILDREN - Zulfa Nida; Eny Purwandari (Universitas Pendidikan Indonesia, 2022)
This study aims to test the effectiveness of the mnemonic method on the ability to read hijaiyah letters in mentally disabled children. The design used in this study is an interrupted time series design. The research subjects were 3 mentally disabled students at SMPLB Siwi Mulia Madiun. Measurement of the ability to read hijaiyah letters in students was carried out repeatedly before and after treatment to see the consistency of the condition of the research subject. The normality test in this study used the Shapiro-Wilk test with a significance value of 0.56, which means the data is usually distributed. Meanwhile, the hypothesis testing used the paired sample T-test with a score (t = -18.0, p = 0.003), (t = -5.9, p = 0.027), (t = -11.1, p = 0.008) or all p values were smaller than 0.05 means that there is a significant difference between the results of the pre-test and post-test, where the post-test score is higher than the pre-test score. The findings of this study proved that effective mnemonic methods improve the ability to read hijaiyah letters in mentally disabled children.